The Constitutionality of the Proposal to Extend the Term of Office of Village Heads in the Principles of Democracy - Muhammad Mubarok; Siti Rodhiyah Dwi Istinah (UNISSULA Semarang, 2025)
Abstract. The extension of the village head’s term of office emerged following numerous demonstrations by village heads. Article 39 of the Village Law stipulates that the Village Head holds office for six years from the date of inauguration. A Village Head may serve a maximum of three consecutive or non-consecutive terms. However, the Village Head rejected this provision and requested that Article 39 of the Village Law be revised, allowing the village head’s term of office to be extended from six years to nine years. This is despite Constitutional Court Decision No. 42/PUU-XIX/2021 providing a constitutional interpretation of the term limit for Village Heads. This study aims to address the constitutionality of the Village Head’s term limit following the Constitutional Court Decision and its impact on village law and governance. This research utilizes both a legislative and conceptual approach. The research findings indicate that the limitation on the term of office of Village Heads in Constitutional Court Decision No. 42/PUU-XIX/2021 was implemented based on democratic principles and the spirit of the limitations required by the 1945 Constitution, modeled on the positions of President and Regional Heads. Furthermore, the urgency of extending this term of office is based on the need to increase productivity, complete village development, and reduce post-election polarization. However, negative implications such as the potential for authoritarianism, abuse of power, and stagnation in leadership regeneration make this proposal controversial. Furthermore, excessively long term extensions can lead to political saturation and reduced community participation in village democracy.